Obstructing intestinal cocooning with Familial Mediterranean Fever - A. ElRifai; S. Akel (Elsevier, 2019)
This is a case report of a 17 years old female known to have Familial Mediterranean fever who presented to the emergency department with one-day history of severe epigastric pain and non-bilious vomiting. The patient was known to be non-compliant with her treatment and was admitted for disease management and pain control. However, the pain persisted over the next 48 h and the patient developed bilious vomiting. CT scan with IV and Oral contrast was done which revealed proximal jejunal obstruction. The patient was taken to the OR for laparotomy and release of adhesions. She was found to have cocooning of her bowels, no resection was needed. She did well postoperatively and was discharged home POD 4. Keywords: Familial Mediterranean fever, Obstruction, Laparotomy